Anticariogenic activity of marine brown algae Padina boergesenii and its active components towards Streptococcus mutans - Sangavi, Ravichellam; Malligarjunan, Nambiraman; Satish, Lakkakula; Raja, Veerapandian; Pandian, Shunmugiah Karutha; Gowrishankar, Shanmugaraj (Frontiers in Cellular and Infection Microbiology, 2024)
Streptococcus mutans is a well-recognized bacterium that plays a predominant role in the progression of dental caries. Its pathogenicity is linked to several key characteristics, including the ability to produce organic acids (acidogenicity), thrive in low pH environments (aciduricity), synthesize exopolysaccharides (EPS) via glucosyltransferases, and form retentive biofilms. The treatment of dental caries with conventional antibiotics is often ineffective due to the bacterium’s capacity to form recalcitrant biofilms. To address these challenges, strategies that specifically target the pathogen’s virulence without affecting its viability have emerged as promising alternatives. In this context, we investigated the anticariogenic properties of the methanolic extract of Padina boergesenii (MEPB). MEPB demonstrated substantial, dose-dependent antibiofilm activity, with a maximum inhibition of 93% at 128 μg/mL, without compromising the viability of S. mutans. Anti-virulence assays using sub-MIC (minimum inhibitory concentration) levels of MEPB showed significant reductions in key virulence factors: 75% reduction in sucrose-dependent adherence, 65% reduction in sucrose-independent adherence, along with notable decreases in acid production, acid tolerance, and water-insoluble (85%) and water-soluble (52%) glucan synthesis. Additionally, MEPB significantly reduced cell surface hydrophobicity (55%) and extracellular DNA (eDNA) production (64%). qPCR analysis corroborated these in vitro findings, revealing that MEPB suppresses the expression of genes involved in S. mutans virulence, particularly genes related to EPS synthesis (gtfB, gtfC & gtfD) biofilm formation(gbpB & gbpC) and two-component regulatory system (vicR) were downregulated. Toxicity testing on human buccal epithelial cells confirmed the non-toxic nature of MEPB, suggesting its safety for potential therapeutic use. Furthermore, GC-MS/MS analysis identified palmitic acid, myristic acid, and stearic acid as the major active constituents of the MEPB extract. Subsequent biofilm inhibitory assays confirmed the potent antibiofilm efficacy of these compounds: palmitic acid (85%), myristic acid (72%) and stearic acid (83%). In conclusion, this study identifies P. boergesenii and its active biomolecules as potential anticariogenic agents, offering an alternative approach to combat dental caries by targeting bacterial virulence mechanisms rather than viability.